ANÁLISE DE DADOS DE SOBREVIVÊNCIA ESPACIALMENTE CORRELACIONADOS - MÁQUINA, Calisto Manuel; DEMARQUI, Fábio Nogueira; PRATES, Marcos Oliveira; SANTOS, Nerilson Terra (Brazilian Journal of Biometrics, 2019)
A survival frailty model for spatially correlated lifetime data is discussed. By considering a completely parametric Bayesian approach, the intrinsically conditional autoregressive (ICAR) model is assumed for the frailty distribution, whereas the base distribution of lifetimes is modeled by the Weibull distribution. A Bayesian model selection criterion is discussed. A detailed description of how to use the R software along with OpenBUGS software to carry out inferences on the survival frailty model is provided. The analysis of a real data set involving patients diagnosed with bladder cancer in the state of Connecticut, USA, is presented.